Flux, unrelenting – the struggle for local seed sovereignty in Nicaragua. Issue 4 (6th June 2020) - Müller, Birgit
ABSTRACT: Most farmers are not activists. They make, however, their own sense of the world and act – sometimes quite stubbornly – according to that sense given, grasping what they perceive as opportunities, and protecting what they feel as essential for their livelihood. Political projects for Nicaraguan society, international policy-making, corporate strategies and imperial ambitions engage with and affect the varieties grown locally. The article analyses the creativity and political potential, as well as the contradictions and inconsistencies of the quotidian practice of seed saving under extreme constraint in light of the major struggles about Nicaraguan seed legislation.